Ḥadīths on al-Taṣwīr and Ittijāhāt al-ʿUlamāʾ concerning handmade image-making - Mohd Hamdan, Muhammad Akmalludin; Fettane, Amar (IIUM Press, 2021)
ABSTRACT: This research is concerned with the issues pertaining to image-making while aiming to understand the trends amongst the scholars in dealing with the subject. The divergence of opinions between scholars since the early time of Islam until today substantiates the significance of this particular research. The researchers start by searching for and collecting the most important ḥadīths and verify them based on the standard ḥadīth verification principles. The second step is to analyse the debate amongst the scholars, as well as to compare the position of the scholars in this particular matter, with some academic appraisals on their respective stance. The inductive and analytical methods are utilised in the entire study. As the outcome of this research, the researchers conclude that the dispute amongst the scholars in this matter is not due to the status of the ḥadīths, i.e., whether they are authentic, weak, or fabricated, but the dispute was based entirely on their differences in understanding the ḥadīths and their reasoning. This, as it is well-known, is considered as a branch of the ḥadīth sciences which is fiqh al- ḥadīth.